Law Enforcement against Corporations for Wildlife Crimes which are Protected Under the Constitution of the Republic Indonesia Number 5 of 1990 - Arnovan Pratama Surbakti; Yasmirah Mandasari Saragih; Sumarno Sumarno (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Indonesia is rich in diverse natural resources, namely animal natural resources and vegetable natural resources. One of the gifts of Almighty God which can be used as a source of the country's economy for national development. However, as time goes by, the species that breed in the forest are starting to become endangered. This is caused by the behavior of people or business entities who only think about personal interests without thinking about the impact of what they have done. A corporation involved in crimes involving protected wild animals will be charged in accordance with the applicable articles to provide a deterrent effect against the perpetrators. This research aims to find out the types of crimes against protected wild animals and to find out how law enforcement is carried out against corporations that commit crimes against protected wild animals based on Law of the Republic of Indonesia Number 5 of 1990 concerning Conservation of Living Natural Resources and Their Ecosystems. This research is normative legal research. The data collection method is by conducting a literature review of legal materials whose data sources come from secondary legal materials, namely primary legal materials, secondary legal materials and tertiary legal materials. The data is described qualitatively descriptively and then analyzed to obtain conclusions from the problem formulations.